2017
DOI: 10.1111/jcpe.12690
|View full text |Cite
|
Sign up to set email alerts
|

Gingivitis and lifestyle influences on high‐sensitivity C‐reactive protein and interleukin 6 in adolescents

Abstract: In this study, hs-CRP was positively associated with gingivitis, smoking daily and overweight/obesity among 15-year-olds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Shojaee et al () reported a significant difference and positive correlation between salivary CRP concentrations and periodontitis disease status among healthy subjects. Many studies investigating CRP levels in the serum and GCF found similar results (George & Janam, ; Kanaparthy, Kanaparthy, & Mahendra, ; Pitchika et al, ; Pitiphat, Savetsilp, & Wara‐Aswapati, ). Our study is one of the few studies that compared salivary CRP concentrations of healthy subjects and patients with gingivitis and periodontitis.…”
Section: Discussionmentioning
confidence: 59%
“…Shojaee et al () reported a significant difference and positive correlation between salivary CRP concentrations and periodontitis disease status among healthy subjects. Many studies investigating CRP levels in the serum and GCF found similar results (George & Janam, ; Kanaparthy, Kanaparthy, & Mahendra, ; Pitchika et al, ; Pitiphat, Savetsilp, & Wara‐Aswapati, ). Our study is one of the few studies that compared salivary CRP concentrations of healthy subjects and patients with gingivitis and periodontitis.…”
Section: Discussionmentioning
confidence: 59%
“…Second, control of potential confounders through adequate statistical analyses (e.g., multivariate models) was applied only in some studies. 187,188 Overall, the above mentioned findings seem to demonstrate that the inflammation of marginal gingival tissues determines an increase in systemic inflammation, assessed in terms of CRP levels. However, other studies have failed to demonstrate potentially relevant systemic effects during gingivitis development.…”
Section: Systemic Inflammation Markers (Crp)mentioning
confidence: 78%
“…First, criteria for GC definition varied greatly among studies. Second, control of potential confounders through adequate statistical analyses (e.g., multivariate models) was applied only in some studies . Overall, the above mentioned findings seem to demonstrate that the inflammation of marginal gingival tissues determines an increase in systemic inflammation, assessed in terms of CRP levels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Children born in the Munich centre who had available dental examination data and dietary information were included in this study. Details concerning the study's background, representative recruitment strategy, inclusion and exclusion criteria have been described elsewhere [15][16][17]. In this study, a total of 915 (GINIplus: 557; LISAplus: 358) and 996 (GINIplus: 652; LISAplus: 344) participants were included from the 10-and 15-year follow-ups, respectively.…”
Section: Study Populationmentioning
confidence: 99%